One-Pot Synthesis of Hydroxy Substituted 1,4-Naphthoquinone with 2-Pyrones - Jia, Lixia; Wang, Huimin; Zhao, Hui; Song, Xinyuan; Hu, Junqiong; Shan, Guohua (Asian Journal of Chemistry, 2011)
In the presence of base-catalyzed, Diels-Alder reaction, involving one-pot decarboxylationoxidation reaction of 4-hydroxy-6-methyl-2-pyrone with 1,4-benzoquinone, gave 7-hydroxyl- 5-methyl-1,4-naphthoquinone. In a similar way, 6-chloro-5-hydroxyl-1,4-naphthoquinone was also obtained with a reasonable yield by using environment-friendly catalyst and solvent.